LEARNING PRONUNCIATION WITH SPOTIFY: WHAT DO INDONESIAN UNIVERSITY STUDENTS THINK? - Mulyani, Mulyani; Eridafithri, Eridafithri; Safriani, Zulvia; Trisnawati, Ika Kana; Netta, Ayuna (Jurnal Dedikasi Pendidikan, 2025)
Pronunciation is commonly regarded as one of the most difficult skills for students learning English as a foreign language (EFL). In response, ELF learners have explored various strategies to improve their pronunciation, including by using digital media platforms such as Spotify. EFL learners can utilize Spotify to access authentic English through its music, lyrics, and spoken content. In this present study, the aim is to investigate Indonesian university students’ perceptions, perceived benefits, and challenges associated with using Spotify to support their English pronunciation development. The study also seeks to identify specific Spotify features that aid in this learning process. By employing a descriptive qualitative approach, the study collected data by means of interviews with eight students from the English Education Department at Universitas Bina Bangsa Getsempena (UBBG), Banda Aceh, Indonesia. The participants were selected by using snowball sampling. The findings of the study revealed that in general, most students had positive views regarding Spotify in boosting English pronunciation. They mentioned a number of benefits in terms of lyrics, karaoke mode, and podcasts, such as contributing to enhanced listening skills and vocabulary acquisition, while some students found the podcast feature less effective for developing speaking proficiency. To conclude, Spotify can be a valuable supplementary resource in English pronunciation learning, as it provides an engaging and flexible learning experience for EFL students